2021
DOI: 10.1186/s40168-021-01172-0
|View full text |Cite
|
Sign up to set email alerts
|

A fiber-deprived diet causes cognitive impairment and hippocampal microglia-mediated synaptic loss through the gut microbiota and metabolites

Abstract: Background Cognitive impairment, an increasing mental health issue, is a core feature of the aging brain and neurodegenerative diseases. Industrialized nations especially, have experienced a marked decrease in dietary fiber intake, but the potential mechanism linking low fiber intake and cognitive impairment is poorly understood. Emerging research reported that the diversity of gut microbiota in Western populations is significantly reduced. However, it is unknown whether a fiber-deficient diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 79 publications
(89 reference statements)
3
82
0
Order By: Relevance
“…FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021). Recent studies over the past decade have revealed that many environmental factors, including diet, antibiotic exposure, energy intake and exercise, can dramatically influence the gut microbiota (Du et al, 2021;Giordan et al, 2021;Shi et al, 2021). Dietary fiber has been shown to improve obesity and is considered a potential therapy because it increases microbial fermentation of SCFAs (Schäfer et al, 2021;Thomson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021). Recent studies over the past decade have revealed that many environmental factors, including diet, antibiotic exposure, energy intake and exercise, can dramatically influence the gut microbiota (Du et al, 2021;Giordan et al, 2021;Shi et al, 2021). Dietary fiber has been shown to improve obesity and is considered a potential therapy because it increases microbial fermentation of SCFAs (Schäfer et al, 2021;Thomson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…6 In this regard, emerging evidence suggests that diets low in dietary fiber content are associated with cognitive impairments. 7 Dietary fiber is associated with a reduced cardiovascular disease and all cancer risk, highlighting its importance as part of a healthy diet. 8,9 In the United States, more than 90% of women and 97% of men among adults do not meet current recommends for dietary fiber intake.…”
Section: Introductionmentioning
confidence: 99%
“…Proteobacteria includes many notorious pathogens, including Escherichia, Shigella , and Salmonella , all in the Gammaproteobacteria. An elevated relative abundance of the phylum is associated with worse cognitive performance or impairment in clinical [ 48 , 49 ], population-based [ 50 , 51 ], and animal studies [ 52 ], in addition to being considered a marker of gut dysbiosis [ 53 ]. Our findings suggest that in addition to the direct negative relationship between Proteobacteria relative abundance and cognitive scores observed in prior studies, it may modify the associations of caffeine and acetaminophen with cognition in an adverse manner.…”
Section: Discussionmentioning
confidence: 99%